Salinity tolerance of eggs and larvae of the mangrove red snapper (Lutjanus argentimaculatus) - Estudillo, Mary Chona Belen (College of Fisheries, U. P. in the Visayas, 1998)
A series of experiments was carried out to evaluate the salinity preferences of eggs and larvae of Lutjanusargentimaculatus during ontogeny. L. argentimaculatus eggs at morula, embryonic shield and eyed stage were transferred directly to five salinity gradients (8, 16, 24, 32 and 40 ppt). Egg transferred at morulaaand eyed stage showed significantly high tolerance to salinity changes than those transferred at embryonic shield stage. The eggs developed and hatched in all salinities regardless of the embryonic stage at transfer. Embryonic development was delayed and hatching peak was relatively longer at salinities of 8, 16 and 24 ppt, than at 32 and 40 ppt. Larval length and yolk volume at hatching did not vary significantly with salinity. No significant relationship was observed between yolk resorption and larval growth at varying salinities. Percentages of viable larvae increased with increasing salinities, while a negative correlation existed between percentages of abnormal larvae and salinities indicating that the optimum salinity range for egg incubation is 32 and 40 ppt. Tolerance of L. argentimaculatus larvae to salinity, changed with age.. Newly hatched larvae tolerated abrupt change of salinity from 8 to 40 ppt than 7-, 14- or 21-day old larvae. High tolerance to abrupt salinity change increased starting on day 28. Regardless of age, L. argentimaculatus larvae consistently showed longer LT50 when apruptly transferred to 16 ppt. Long-term effect of salinity (larval rearing) gave no significant differences on growth and survival rates during the first rearing phase (day 0-21) and second phase of rearing (day 22-50). However, the condition factor (K) of larvae reared at lower salinities was significantly higher compared to those at 40 ppt indicating that the larvae reared at 40 ppt were leaner (P<0.05). Gill epithelia of 42- and 50-day old larvae showed increased size and density of chrloride cells (CC) at higher salinities (32 and 40 ppt). The increase in size and density of CC at salinities of 32 and 40 ppt compared to CC at salinities of 24 and 16 ppt indicate the osmoregulatory function of the CC at higher salinities